Peran Interaksi Media Sosial Terhadap Future Intention - Muhammad Ikhsan Fifaldyovan (CiDEA Journal, 2024)
This study aims to analyze the positive impact of social media interaction (source credibility, source homophily and content quality) on future intention. The study used a quantitative approach involving 120 online travel agent consumers in Semarang, obtained by purposive sampling. Data were obtained by online questionnaires and then analyzed by multiple linear regression analysis. The study results are that source credibility has a positive effect on future intention, source homophily has a positive effect on future intention, and content quality has a positive effect on future intention. The study concludes that social media interaction (source credibility, source homophily, and content quality) positively impacts future intention.